Standalone solar streetlamp sharing an interactive buck-boost converter - Wook Park, Jin; seo hyun, Yeo; Yun Soen, Ho; Mi Park, Seong; Jun Park, Sung; Heon Kim, Gwang (International Journal of Engineering and Technology, 2018)
Background/Objectives: Typically, the stand-alone solar streetlight system is used independently of DC/DC converter for battery charging and for LED lighting control. Such an independent power conversion system uses a DC/DC converter with only a voltage raising or reducing function for cost reduction (power semiconductor, inductor, capacitor, etc.). However, these DC/DC converters have limitations on efficiency increase in all voltage ranges when controlling MPPT. In addition, DC/DC converters for LED lighting have limitations in the design of the lighting voltage because the LED lighting operates only at voltages lower or higher than the battery voltage. Therefore, In this paper, a new power conversion system using a DC/DC converter for battery charging and for streetlight using a bi-directional buck and boost DC/DC converter.Methods/Statistical analysis: A prototype was fabricated and tested. The used equipment was a Tektronix oscilloscope, 24V (Lead-Acid) Battery, PV Simulator (ETS 1000X10D PVF_Sorensen) and WT 3000 (YOKOGAWA).Findings: By using a shared converter, cost savings were achieved by reducing the number of power semiconductor devices and the number of inductors and capacitors. In addition, it works as an input / output step-down converter to compensate the voltage design limit.Improvements/Applications: In <30 words.Â Â